Discovering the sense of touch: protocol for a randomised controlled trial examining the efficacy of a somatosensory discrimination intervention for children with hemiplegic cerebral palsy - Belinda McLean; Misty Blakeman; Leeanne Carey; Roslyn Ward; Iona Novak; Jane Valentine; Eve Blair; Susan Taylor; Natasha Bear; Michael Bynevelt; Emma Basc; Stephen Rose; et al. (BMC, 2018)
Abstract Background Of children with hemiplegic cerebral palsy, 75% have impaired somatosensory function, which contributes to learned non-use of the affected upper limb. Currently, motor learning approaches are used to improve upper-limb motor skills in these children, but few studies have examined the effect of any intervention to ameliorate somatosensory impairments. Recently, Sense© training was piloted with a paediatric sample, seven children with hemiplegic cerebral palsy, demonstrating statistically and clinically significant change in limb position sense, goal performance and bimanual hand-use. This paper describes a protocol for a Randomised Controlled Trial of Sense© for Kids training, hypothesising that its receipt will improve somatosensory discrimination ability more than placebo (dose-matched Goal Directed Therapy via Home Program). Secondary hypotheses include that it will alter brain activation in somatosensory processing regions, white-matter characteristics of the thalamocortical tracts and improve bimanual function, activity and participation more than Goal Directed Training via Home Program. Methods and design This is a single blind, randomised matched-pair, placebo-controlled trial. Participants will be aged 6-15 years with a confirmed description of hemiplegic cerebral palsy and somatosensory discrimination impairment, as measured by the sense©_assess Kids. Participants will be randomly allocated to receive 3h a week for 6 weeks of either Sense© for Kids or Goal Directed Therapy via Home Program. Children will be matched on age and severity of somatosensory discrimination impairment. The primary outcome will be somatosensory discrimination ability, measured by sense©_assess Kids score. Secondary outcomes will include degree of brain activation in response to a somatosensory task measured by functional MRI, changes in the white matter of the thalamocortical tract measured by diffusion MRI, bimanual motor function, activity and participation. Discussion This study will assess the efficacy of an intervention to increase somatosensory discrimination ability in children with cerebral palsy. It will explore clinically important questions about the efficacy of intervening in somatosensation impairment to improve bimanual motor function, compared with focusing on motor impairment directly, and whether focusing on motor impairment alone can affect somatosensory ability. Trial registration This trial is registered with the Australian New Zealand Clinical Trials Registry, registration number: ACTRN12618000348257. World Health Organisation universal trial number: U1111-1210-1726.